2010
DOI: 10.1001/archgenpsychiatry.2010.101
|View full text |Cite
|
Sign up to set email alerts
|

Individuals, Schools, and Neighborhood

Abstract: The association between urbanicity and psychosis appears to be a reflection of increased social fragmentation present within cities. The qualitative interactions observed are consistent with a hypothesis that certain characteristics that define individuals as being different from most other people in their local environment may increase risk of psychosis. These findings have potentially important implications for understanding the etiology of psychotic disorders and for informing social policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(88 citation statements)
references
References 50 publications
(70 reference statements)
5
81
1
1
Order By: Relevance
“…Consistent with previous research suggesting low general neighborhood effects in total population samples, 13 we found that such effects accounted for merely 2% and 3% of variance in schizophrenia and depression, respectively. When we subsequently estimated family-adjusted general neighborhood effects that additionally accounted for the strong familial correlations in neighborhood residence (eg, 79% of the siblings lived in the same neighborhoods at age 15), we observed that neighborhoods did not account for significant variation in schizophrenia but accounted for about 2% in depression.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous research suggesting low general neighborhood effects in total population samples, 13 we found that such effects accounted for merely 2% and 3% of variance in schizophrenia and depression, respectively. When we subsequently estimated family-adjusted general neighborhood effects that additionally accounted for the strong familial correlations in neighborhood residence (eg, 79% of the siblings lived in the same neighborhoods at age 15), we observed that neighborhoods did not account for significant variation in schizophrenia but accounted for about 2% in depression.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we found that sibling similarities explained half of the variance in schizophrenia and a fifth of the variance in depression. In line with systematic reviews and population-based studies examining associations of neighborhood influences on nonaffective psychotic disorders and depression, 3,6,10,13,23 population density and neighborhood deprivation predicted both schizophrenia and depression in the population. However, in subsequent analyses of the same associations, when accounting for unobserved familial risk factors by studying differentially exposed cousins and siblings, we found that effects decreased substantially within extended families (cousin comparisons) and were entirely attenuated within nuclear families (sibling comparisons).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Having a minority status, in terms of a defining social characteristic that differs from others in a locality, has been associated with an increased risk of mental illness (van Os et al 2010; Zammit et al 2010; Shaw et al 2012). Most studies, to date, define minority status in terms of ethnicity where, as the proportion of ethnic minorities in a locality increases – and thus their minority status decreases – the risk of mental illness is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…However, the concept of social fragmentation captures an important yet often overlooked characteristic of the school environment. Previous research has investigated the role of school social fragmentation on psychotic disorders [36], but its role on physical activity has not yet been explored. School-level social fragmentation could influence physical activity through several mechanisms.…”
Section: Introductionmentioning
confidence: 99%